Modeling the Impact of Intersection Design Configurations on Traffic Flow During Peak Hour in Smart Cities: A Case Study on Urban Roads in Slovakia - Peter Bindzar; Daniela Marasova; Jaroslaw Brodny; Magdalena Tutak; Robert Ulewicz; Ales Sliva (IEEE Access, 2024)
The aim of this article is to gain valuable insights into the performance and effectiveness of intersection design configurations and their impact on traffic flow during peak hour in urban road networks. The study focuses on a case study in the second largest city of the country, and considers three different scenarios: 1) replacing some of the signalized intersection with a roundabout; 2) replacing all signalized intersections with roundabouts; and 3) optimizing the signal plans of existing signalized intersections. The study uses mesoscopic simulation and measures traffic flow efficiency, including delays and queues, to analyze and compare the performance of each scenario. The research methodology involves conducting a comparative analysis of different scenarios, as well as data collection, traffic surveys, and the creation of simulation models using the PTV Vissim software. The results indicate that the most effective solution is to modify signal plans while preserving the traditional signalized intersections. The research also provides insights into the advantages and disadvantages of different intersection designs, which can aid decision-makers in selecting and implementing the most appropriate solution to accommodate evolving traffic demands in urban areas.